Physical Education Teacher Ability to Utilize Technology for Conducting Distance Learning in New Normal Period - Pirdaus, Atep Ramlan; Mahendra, Agus; Lubay, Lukmanul Hakim (TEGAR: Journal of Teaching Physical Education in Elementary School, 2021)
Covid-19 pandemic, at the beginning of 2020, made the government implement distance learning to prevent the spread of the COVID-19 virus. In distance learning, the Physical Education learning process, which was initially conducted through face-to-face learning methods, is facilitated by technology so that Physical Education learning can be well-conducted. This study aimed to determine the ability of Elementary School Physical Education teachers to utilize technology in distance learning during the new normal period. The method used was descriptive research. The subjects of this study were 22 public Elementary School Physical Education teachers of a sub-district in Bandung city. The instrument used was Quality matter 2014. The results showed that Physical Education teachers' ability in elementary schools to utilize technology for distance learning during the new normal period was in the fair category.